Keterwakilan Perempuan dalam Pemilihan Umum Legislatif di Kabupaten Manggarai Timur Tahun 2019 - Selfiana Lanut; Hernimus Ratu Udju; Cyrilius Wilton Lamataro (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
The implementation of the efficiency policy of affirmation policy in Indonesia provides room for 30% of the number of women legislative candidates who are advancing at the regional and central levels. The policy is realized in the regulation of political contestation in Law No. 7 of 2017 concerning elections. The KPU and political parties must be able to ensure that the fulfillment of this regulation takes place for the sake of fair elections. However, the existence of this Law does not necessarily make women's representation pass the Legislative general election. This research is an empirical research, namely field research in this case using primary data and secondary data. Primary data was obtained from the results of interviews with respondents. Secondary data is obtained from books, laws and regulations, and the internet. The results of this study show that 1) Women's representation in the legislative general election in East Manggarai district in 2019 has met the 30% quota, but only 1 person from 157 female legislative candidates has qualified to become a legislative member. 2) Factors that inhibit women's representation in the legislature are legal structure, legal substance and legal culture.